Caregiver Perspectives on a Child's Diagnosis of 3q29 Deletion: "We Can't Just Wish This Thing Away". Issue 2 (27th February 2022) - Glassford, Megan R.; Purcell, Ryan H.; Pass, Sarah; Murphy, Melissa M.; ,; Bassell, Gary J.; Mulle, Jennifer G.
ABSTRACT: Objective: Genetic diagnoses are increasingly common in cases of intellectual disability and developmental delay. Although ascertainment of a relatively common, well-studied variant may provide guidance related to treatments and developmental expectations, it is less clear how the diagnosis of a rare variant affects caregivers, especially when the phenotype may include later-onset manifestations such as psychosis. In this study, we sought to identify caregiver concerns in the first qualitative study to assess the psychosocial impact of diagnosis on caregivers of individuals with 3q29 deletion syndrome (3q29Del), which is associated with a 40-fold increase in risk for psychosis. Methods: Participants were recruited from the national 3q29Del registry housed at Emory University (3q29deletion.org ). Fifteen participants completed a semistructured phone interview during which they were asked about their experiences before, during, and after their child received a diagnosis of 3q29Del. Interview responses were analyzed using the general inductive approach, and overarching themes were identified. Results: We identified the following overarching themes: difficult "diagnostic odyssey, " mixed feelings about diagnosis, frustration with degree of uncertainty, and importance of resources. Importantly, our data suggest that future risk for psychosis is often not disclosed by medical professionals, consistent with the experience of individuals with 22q11.2 deletion syndrome. Conclusions: These results highlight potential gaps in how caregivers are informed of risk for adult-onset conditions and indicate key caregiver concerns for consideration in the diagnosis of 3q29Del.